Current methodological approaches in studying the use of advanced digital technologies in migration management - Nalbandian, Lucia; Dreher, Nick (Frontiers in Human Dynamics, 2023)
The use of technology in migration management has increased in recent years. As such, practitioners and scholars are increasingly interested in the real and potential use of advanced technologies in migration management. This paper offers an early review of academic and grey literature on the use of advanced digital technologies (ADTs) in migration management processes. The primary focus of this review is literature that discusses migration management technologies—ADTs used by institutional actors (governments, NGOs, transnational institutions). This paper is divided into four thematic areas, aimed at providing a summary of major trends in the literature, including research methodologies, types of technologies, purpose of technologies and the migrants impacted by the technologies explored. Based on the literature reviewed, we identify common themes and areas that merit further exploration and research. To close, we offer an early view into the current uses of advanced digital technologies that we have identified in our Migration Tech Tracker, an interactive tool that consolidates the information found in the literature review of the paper including captures the various uses of technology by the diverse range of actors in the migration sector. The paper leverages the information from the Tracker to both indicate where and how emerging technologies are being used to govern migrants and simultaneously to identify ADTs that are being analyzed, reported on and researched and those that remain under-explored.